A biomimetic liver cancer on-a-chip reveals a critical role of LIPOCALIN-2 in promoting hepatocellular carcinoma progression - Peiliang Shen; Yuanyuan Jia; Weijia Zhou; Weiwei Zheng; Yueyao Wu; Suchen Qu; Shiyu Du; Siliang Wang; Huilian Shi; Jia Sun; Xin Han (Acta Pharmaceutica Sinica B, 2023)
Hepatic stellate cells (HSCs) represent a significant component of hepatocellular carcinoma (HCC) microenvironments which play a critical role in tumor progression and drug resistance. Tumor-on-a-chip technology has provided a powerful in vitro platform to investigate the crosstalk between activated HSCs and HCC cells by mimicking physiological architecture with precise spatiotemporal control. Here we developed a tri-cell culture microfluidic chip to evaluate the impact of HSCs on HCC progression. On-chip analysis revealed activated HSCs contributed to endothelial invasion, HCC drug resistance and natural killer (NK) cell exhaustion. Cytokine array and RNA sequencing analysis were combined to indicate the iron-binding protein LIPOCALIN-2 (LCN-2) as a key factor in remodeling tumor microenvironments in the HCC-on-a-chip. LCN-2 targeted therapy demonstrated robust anti-tumor effects both in vitro 3D biomimetic chip and in vivo mouse model, including angiogenesis inhibition, sorafenib sensitivity promotion and NK-cell cytotoxicity enhancement. Taken together, the microfluidic platform exhibited obvious advantages in mimicking functional characteristics of tumor microenvironments and developing targeted therapies.